Prediction of Residues Conferring Assembly of Fimbriae: 3D Structure Modeling of Major Subunit and Chaperone of CS3 Pili - Eskandari, Vajiheh; Yakhchali, Bagher; Arab, Seyed Shahriar (Innovations in Science and Technology Vol. 4, 2022)
The goal of this study is to use computational approaches, namely comparative protein modelling, to simulate the three-dimensional (3D) structures of the major subunit (CstH) and chaperone (CS3-1) of CS3 pili. Gram negative bacteria can produce surface hair-like structures referred to as pili or fimbriae. CstH and CS3-1 models were developed and deposited in the PMDB database with the ID codes PM0079873 and PM0078481, respectively. In order to discover probable interaction sites in the CstH molecule, 3D structures were used in the molecular dimerization. The PDBePISA server was used to calculate the dimer molecules' interaction surface areas. PPEPred server and APBS software were used to determine the interaction affinities and electrostatic potential of the CstH subunit surfaces and complexes, respectively. The findings showed that analysing 3D models provides valuable insight into the permissive sites, binding mode, and contact sites of the CstH protein, and that our method could be useful in further experimental research on pili biology and applications.